STRUKTUR DAN TINGKAT PENDAPATAN RUMAH TANGGA PETANI KARET DI DESA TERATAK KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Sri Sulastri Purnamasari; Yusmini '; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study was (1) to analyze the structure of household income in the village rubber farmers Teratak village Rumbio Jaya district Kampar regency, (2) Analyzing household income levels of farmers rubber Teratak village Rumbio Jaya district Kampar regency. The method used in this study is a survey method and sampling technique that the purposive sampling method. The population in this study was 208 people and is sampled 24 people who fit the criteria. The structure of the income of farmers in the village Teratak samples showed that the agricultural sector is the largest contributor to the total income of farm households is equal to 84,76% and from non-agricultural sectors of 15,24%. Revenues from the agricultural sector dominated from rubber farming income that is equal to 57,81%, the rest of the revenue contributed by 23,04% Oil Farming, Rice Farming of 1,91% and Fish Farm of 2,00%. Average income households that received sample Rp.3.196.605/month which is contributed from the main revenue of Rp.1.847.917/month (57.81%) of the household income, additional income of      Rp.1.211.952/month (37,91%) of the income households, while the income of the farmer family members contributed as much as Rp.136.736/month (4,28%) of the total household income. Keyword : Structure, household income, household, rubber farmers, per capita income